Neutrophil-Camouflaged Stealth Liposomes for Photothermal-Induced Tumor Immunotherapy Through Intratumoral Bacterial Activation - Xinxin Chen; Jiang Sun; Tingxian Ye; Fanzhu Li (Pharmaceutics)
Objective: F. nucleatum, a tumor-resident bacterium colonizing breast cancer (BC), results in an immunosuppressive microenvironment and facilitates tumor growth and metastasis. This study aimed to develop a neutrophil-based liposome delivery system designed for dual-targeted elimination of tumor cells and F. nucleatum, while simultaneously upregulating pathogen-associated molecular patterns and damage-associated molecular patterns to potentiate tumor immunotherapy. Methods: The liposomes (PD/GA-LPs) loaded with the perylene diimide complex (PD) and gambogic acid (GA) were fabricated via the extrusion method. Subsequently, comprehensive evaluations including physicochemical characteristics, antibacterial activity, antitumor effect, and immunomodulatory effect evaluation were systematically conducted to validate the feasibility of this delivery system. Results: The resulting PD/GA-LPs exhibited a dynamic size (121.3 nm, zeta potential −44.1 mV) and a high encapsulation efficiency of approximately 78.1% (PD) and 91.8% (GA). In addition, the optimized PD/GA-LPs exhibited excellent photothermal performance and antibacterial efficacy. In vitro cellular experiments revealed that PD/GA-LPs exhibited enhanced internalization by neutrophils, followed by extracellular trap-mediated release, ultimately significantly inhibiting tumor cell proliferation and inducing immunogenic cell death. During in vivo treatment, PD/GA-LPs exhibited targeted tumor accumulation, where F. nucleatum-driven PD reduction activated near-infrared-responsive photothermal ablation. When combined with GA, this delivery system effectively eliminated tumor cells and F. nucleatum, while facilitating the subsequent T-cell infiltration. Conclusions: This strategy amplified the antitumor immune response, thus leading to effective treatment of BC and prevention of metastasis. In summary, this approach, grounded in the distinct microecology of tumor and normal tissues, offers novel insights into the development of precise and potent immunotherapies for BC.